Sexual Dimorphism in the Age of Genomics: How, When, Where - Deegan, Daniel F.; Engel, Nora (Frontiers in Cell and Developmental Biology, 2019)
In mammals, sex chromosomes start to program autosomal gene expression and epigenetic patterns very soon after fertilization. Yet whether the resulting sexual dimorphism is perpetuated throughout development and how it connects to the sex-specific expression patterns in adult tissues is not known. There is a dearth of information on the timing and continuity of sex biases during development. It is also unclear whether sex-specific selection operates during embryogenesis. On the other hand, there is mounting evidence that all adult tissues exhibit sex-specific expression patterns, some of which are independent of hormonal influence and due to intrinsic regulatory effects of the sex chromosome constitution. There are many diseases with origins during embryogenesis that also exhibit sex biases. Epigenetics has provided us with viable mechanisms to explain how the genome stores the memory of developmental events. We propose that some of these marks can be traced back to the sex chromosomes, which interact with the autosomes and establish sex-specific epigenetic features soon after fertilization. Sex-biased epigenetic marks that linger after reprogramming may reveal themselves at the transcriptional level at later developmental stages and possibly, throughout the lifespan. Detailed molecular information on the ontogeny of sex biases would also elucidate the sex-specific selective pressures operating on embryos and how compensatory mechanisms evolved to resolve sexual conflict.